Infrared photodetector based on GeTe nanofilms with high performance - Vincent Teng (Optics Letters, 2020)
GeTe is an important narrow band gap semiconductor material, which has found application in the fields of thermoelectricity, phase change storage as well as switch. However, it has not been studied for application in the field of photodetectors. Here, GeTe thin films were grown by magnetron sputtering and their material structure, optical and electrical properties were compared before and after annealing. High-performance photodetectors with detectivity of ∼1013 Jones at 850 nm light were demonstrated. Thus the novel, to the best of our knowledge, application of GeTe in optoelectronic devices is reported in this work.